1-(5-Nitro-2-oxoindolin-3-ylidene)thiosemicarbazide - Bandeira, Katlen C. T. (International Union of Crystallography, 2011)
In the title molecule, C9H7N5O3S, there is an intramolecular N—H⋯O. The molecule is essentially planar, with the maximum deviation from the mean plane of the 18 non-H atoms being 0.135 (2) Å for the amine N atom. In the crystal, the molecules are connected via intermolecular N—H⋯O and N—H⋯S hydrogen bonds, forming two-dimensional networks lying parallel to (10). They are separated by an interplanar distance of 3.3214 (9) Å, leading to π–π interactions which stabilize the crystal structure.